2015
DOI: 10.1111/ncmr.12055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attachment Anxiety and Avoidance on Negotiation Propensity and Performance

Abstract: Attachment theory has received scant consideration in the negotiation literature. We examined the effects of attachment anxiety and avoidance on negotiation propensity and performance in two studies. In terms of negotiation propensity (Study 1), attachment anxiety had significant, deleterious effects, though contrary to our predictions, attachment avoidance did not have significant effects. However, there was an interaction such that individuals high on attachment avoidance had a greater propensity to negotiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…They showed that the integrating style was positively related to all personality factors considered, except neuroticism. Another study (Bear & Segel‐Karpas, ) revealed that anxious attachment style had a deleterious effect on negotiation propensity.…”
Section: Discussionmentioning
confidence: 98%
“…They showed that the integrating style was positively related to all personality factors considered, except neuroticism. Another study (Bear & Segel‐Karpas, ) revealed that anxious attachment style had a deleterious effect on negotiation propensity.…”
Section: Discussionmentioning
confidence: 98%
“…We theorized that, in addition to the extent that perceivers came to disrespect an outgroup based on their beliefs about that outgroup's low self-regard, they might also be less inclined to recommend ethical and civil treatment of the group in subsequent interactions. Indeed, previous work has shown a link between lower perceived regard and worse treatment: for example, in negotiations, the less regard individuals ascribe a counterpart, the more likely they are to engage in aggressive and deceptive tactics, and the less likely they are to share information (typically resulting in less 'integrative' outcomes that would generate value; Bear & Segel-Karpas, 2015;Janoff-Bulman & Werther, 2008;Kray, Kennedy, & Van Zant, 2014;Olekalns & Smith, 2009;SimanTov-Nachlieli, Har-Vardi, & Moran, 2020). Thus, in Study 2A, we were able to test the links between a group's behavior to perceptions of its self-worth to both respect for that group and willingness to extend it good treatment.…”
Section: Studies 2a-b: People-for-moneymentioning
confidence: 99%
“…Individual differences that lead to a greater propensity to negotiate include feeling more (vs. less) powerful (Magee et al., ) as do a combination of high perceived ability to initiate the negotiation, as well as beliefs about own negotiation skill (Reif & Brodbeck, ). Another study found that propensity to negotiate is related to attachment orientation at the intra‐ and interpersonal level, such that individuals who were high on attachment avoidance, one's trust in others’ willingness and ability to offer support, had a greater propensity to negotiate with an anxious and avoidant counterpart (Bear & Segel‐Karpas, ).…”
Section: Negotiation and Conflict Managementmentioning
confidence: 99%